Analisis Sistem Informasi Akuntansi Penjualan Untuk Meningkatkan Pengendalian Internal (Studi pada Toko Spare Part dan Oli Tri Jaya) - Silvia Indrarini; Christe Vany Gunawan (Akubis : Jurnal Akuntansi dan Bisnis, 2022)
The purpose of this study was to analyze the sales accounting information system to improve internal control at Spare Part Stores and Oli Tri Jaya. The type of research is case study. Methods of data collection, literature study and field study. Data collection techniques in the form of observation, interviews, and documentation. The problem faced is the weak sales accounting information system. This is evidenced by the dual cash function with the accounting function; documents used are incomplete; and the accounting records used are incomplete. The reason, limited resources and lack of understanding of the company about the importance of sales accounting information systems. As a result, companies may suffer losses or lose assets due to misrepresentation of data and delays in submitting information regarding cash and credit sales. The results of the qualitative descriptive analysis by improving the organizational structure, separating the cash section from the accounting department, adding documents in the form of three copies of cash and credit sales invoices with printed serial numbers, adding warehouse cards, accounts receivable cards, display goods stock cards, financial reports, along with improving systems and company sales procedures so that internal control can run effectively.